2015
DOI: 10.1093/ntr/ntv029
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Hookah Use

Abstract: Background: Potential harms associated with hookah smoking are largely unrecognized and it is emerging as a trendy behavior. To help inform policy and preventive interventions, we used responses from a population survey of US adults to examine risk factors associated with hookah involvement. Method: An online survey of 17 522 US adults was conducted in 2013. The nationally representative sample was drawn from GfK Group's KnowledgePanel plus off-panel recruitment. Multinomial logistic regression was used to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
4
14
0
Order By: Relevance
“…Consistent with the literature (Barnett, Smith, et al, 2013; Cavazos-Rehg, et al, 2015; Salloum, et al, 2015), the results of the current study show that ever hookah smoking is more common among young, educated, non-heterosexual, and other, non-Hispanic, adults. The popularity of hookah smoking among young and college-educated adults is emphasized by the strategic placement of hookah establishments in close proximity to college campuses (Kates, et al, 2016), exposure to online and social media advertisement (Krauss, et al, 2015; Primack, et al, 2012), and the use of flavors attractive to young people (Akl, et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with the literature (Barnett, Smith, et al, 2013; Cavazos-Rehg, et al, 2015; Salloum, et al, 2015), the results of the current study show that ever hookah smoking is more common among young, educated, non-heterosexual, and other, non-Hispanic, adults. The popularity of hookah smoking among young and college-educated adults is emphasized by the strategic placement of hookah establishments in close proximity to college campuses (Kates, et al, 2016), exposure to online and social media advertisement (Krauss, et al, 2015; Primack, et al, 2012), and the use of flavors attractive to young people (Akl, et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to findings from 2013 (Cavazos-Rehg, et al, 2015), we estimated that about 16% of U.S. adults have tried hookah, even once in their life in 2014–2015. The prevalence of ever hookah smoking in the current study was higher than that rates in reported in NATS in 2012–2013 (12.3%) (Agaku, et al, 2014) in 2009–2010 (9.8%) (Salloum, et al, 2015) and that estimated using the Social Climate Survey of Tobacco Control in 2010 (8.8%) (McMillen, et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Emerging adults have a higher risk for hookah use, relative to younger and older age groups (Cavazos-Rehg, Krauss, Kim, & Emery, 2015; Grekin & Ayna, 2012; Smith et al, 2011). In the U.S., recent research demonstrated that 25% of emerging adults reported lifetime hookah use (Villanti, Cobb, Cohn, Williams, & Rath, 2015), and demonstrated that 10% of college students reported past 30-day use (Jarrett, Blosnich, Tworek, & Horn, 2012).…”
Section: Introductionmentioning
confidence: 99%